2021
DOI: 10.3390/pathogens10030319
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Candida Infections in Neonates after Major Surgery: Current Evidence and New Directions

Abstract: Infections represent a serious health problem in neonates. Invasive Candida infections (ICIs) are still a leading cause of mortality and morbidity in neonatal intensive care units (NICUs). Infants hospitalized in NICUs are at high risk of ICIs, because of several risk factors: broad spectrum antibiotic treatments, central catheters and other invasive devices, fungal colonization, and impaired immune responses. In this review we summarize 19 published studies which provide the prevalence of previous surgery in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 107 publications
0
12
0
3
Order By: Relevance
“…The serological test results for Candida mannan antigen, antibody, and 1,3- β -d-glucan (BDG) were negative, while that of galactomannan (GM) was positive. Candida organisms can colonize the mouth and skin [ 12 , 13 ]. The culture samples were sputum obtained from nonsterile sites, which could be contaminated with oral pathogens, suggesting that, in these patients, Candida albicans could be part of the microbiota and not the causative pathogen of the infection.…”
Section: Discussionmentioning
confidence: 99%
“…The serological test results for Candida mannan antigen, antibody, and 1,3- β -d-glucan (BDG) were negative, while that of galactomannan (GM) was positive. Candida organisms can colonize the mouth and skin [ 12 , 13 ]. The culture samples were sputum obtained from nonsterile sites, which could be contaminated with oral pathogens, suggesting that, in these patients, Candida albicans could be part of the microbiota and not the causative pathogen of the infection.…”
Section: Discussionmentioning
confidence: 99%
“…Recent population-based surveillance studies have shown an increasing incidence of invasive candidiasis in the neonatal ICU during the past decade [ 6 , 7 ]. An increased survival rate of extremely preterm neonates with long-term hospitalization and the widespread use of broad-spectrum antibiotics may account for the increasing incidence of invasive candidiasis [ 8 , 9 , 10 ]. Furthermore, more antifungal prophylaxis and the empiric use of echinocandins are reported to be associated with a continuous shift from C. albicans to various non- albicans Candida candidemia, which are more likely to be azole-resistant [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…There have been numerous studies that describe the epidemiology, clinical features, antifungal treatment, and outcomes of neonates with candidemia [ 6 , 7 , 8 , 9 , 10 ]. However, few researchers have investigated the reasons for the treatment failure of neonatal candidemia [ 5 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Congenital anomalies -also known as congenital disorders, congenital malformations, or birth defects -refer to the groups of structure, function, or metabolism abnormalities that cause physical or mental disabilities in newborns. Many of these congenital anomalies can be treated or improved with cost-effective and safe methods that improve long-term outcomes (4)(5)(6). Surgery is an important and life-saving health service that can treat many of these congenital anomalies (7,8).…”
Section: Introductionmentioning
confidence: 99%